RHEUMATOID ARTHRITIS (theoretical aspects) - Golijan, Radojka (ACADEMIC REVIEW, 2023)
The paper presents the theoretical aspects of Rheumatoid arthritis, which is a systemic disease of the joints and connective tissue. It is assumed that almost 1% of the world's population has some form of this disease. Rheumatoid arthritis most often affects the joints, but also internal organs, the heart, kidneys and nervous system, which is why it belongs to systemic connective tissue diseases. The disease begins with an inflammatory reaction on the joint, affects the joint sheaths, leads to exudation and effusion in the joint spaces, which is manifested by signs of inflammation, namely: redness, pain, swelling, impaired joint function. If all therapeutic measures are not taken in this acute phase, the disease slowly begins to "calm down", because it loses these signs of acute inflammation, but only then, in the apparent phase of rest, do changes occur that are much more severe and move into a chronic phase with permanent consequences. This is the destruction of joint surfaces, thickening of the joint capsule, limitation in movement, deformity and stiffness - ankylosis of the joint.